EUTHANASIA: AN ISLAMIC ETHICAL PERSPECTIVE - Nikookar, Hamid Reza; Sooteh, Seyed Hassan Jaafarian (European Scientific Journal, ESJ, 2014)
The popular Egyptian scholar Sheikh Yusuf al-Qaradawi, recently issued a fatwa, or religious ruling, equating euthanasia with murder, but allowing the withholding of treatment that is deemed useless. Egypt Sharia courts and qadis are run and licensed by the Ministry of Justice. The personal status law that regulates matters such as marriage, divorce and child custody is governed by Sharia. In a family court, a woman’s testimony is worth half of a man’s testimony. One of the most important factors which determines society’s attitude towards euthanasia is religion. As there are various sects and tariqas (manner, creeds) in Islam that cause significant differences, it is important to begin with an overall review of Islamic approach to euthanasia. But there are important differences between Islamic countries. The first group contains the countries which are governed by Islamic rules. These countries accept sheria (the code of law derived from the Quran and from the teachings and example of Prophet Mohammed) as their legal and administrative code, like Iran and Saudi Arabia. In Iran Shia Muslims and in Saudi Arabia Sunni Muslims as sects of Islam, rule the State. The second group consists of countries which have secularly governed states, but their laws are based on sheria, like Egypt. Today, many social institutions especially the mass media severely criticize physicians’ attitudes in Turkey. Sometimes these criticisms turn out to be unfair attacks on medicine.